RANCANG BANGUN APLIKASI GAME EDUKASI PENGENALAN HURUF ALFABET DENGAN TEKNOLOGI AUGMENTED REALITY BERBASIS ANDROID - Wicaksana, Rizki Alief; Pangaribuan, Hotma (LPPM Universitas Putera Batam, 2020)
Educational games have very high potential for increasing motivation in learning process. Besides increasing motivation, educational games also have advantages compared to e-learning methods, easier to understand and more interesting. The design of this game will prioritize the process of teaching and learning using the concept of